Organosulfur Compounds as Soil Urease Inhibitors and Their Effect on Kinetics of Urea Hydrolysis - Salehuddin, N.F. (Springer Science and Business Media Deutschland GmbH, 2021)
The application of urea fertilizer on soil surfaces causes hydrolysis reactions to occur rapidly, thus releasing ammonia gas to the atmosphere and, in turn, reducing the availability of nitrogen for plant uptake. The urease inhibitor application with urea is considered a mitigation method to reduce the loss of nitrogen. Chemical-based urease inhibitors effectively reduce nitrogen loss, but they also demonstrate adverse side effects on plants. Thus, there is a need to discover potential candidates for urease inhibitors from natural sources. This study evaluates the potential of organosulfur compounds from garlic, namely, allicin, diallyl sulfide (DAS), and diallyl disulfide (DADS), as inhibitors to urea hydrolysis. The effect of allicin, DAS, and DADS on kinetic parameters of soil urease and urea hydrolysis rate was evaluated using the LineweaverâBurk plot and incubation study. All tested organosulfur compounds exhibited mixed-type inhibition with a high Michaelis constant (Km) and low maximum velocity of reaction (Vmax), compared with control (urea). The calculated inhibitory (dissociation) constant (Ki) for allicin, DAS, and DADS were 0.53, 0.92, and 0.40Â mM, respectively. This indicates that DADS is the most potent soil urease inhibitor, followed by allicin and DAS. After DADS treatment, about 46 of the urea-nitrogen (N) content remained after 21Â days. Meanwhile, allicin and DAS treatments retained urea-N in the soil for 7 and 11Â days, respectively. The results demonstrate that DADS is more effective in delaying enzymatic urea hydrolysis compared with allicin and DAS and showed a high potential as a bio-based urease inhibitor in agriculture. Â© 2021, Sociedad Chilena de la Ciencia del Suelo.